Cardiovascular disease in systemic lupus erythematosus is associated with increased levels of biomarkers reflecting receptor-activated apoptosis. (March 2018) - Wigren, Maria; Svenugnsson, Elisabet; Mattisson, Ingrid Yao; Gustafsson, Johanna T.; Gunnarsson, Iva; Zickert, Agneta; Elvin, Kerstin; Jensen-Urstad, Kerstin; Bengtsson, Anders; Gullstrand, Birgitta; Fredrikson, Gunilla Nordin; Nilsson, Jan
Abstract: Background and aims: There is convincing evidence that adaptive immune responses affect the development of atherosclerosis and thrombosis and several autoimmune diseases are associated with increased cardiovascular risk. However, our understanding of the underlying mechanisms remains limited. We investigated how biomarkers reflecting four aspects of autoimmunity: apoptosis, inflammation, tissue degradation and repair, associate with cardiovascular disease (CVD) in subjects with systemic lupus erythematosus (SLE). Methods: We investigated 484 well-characterized SLE patients, 69 of whom had CVD (coronary artery disease, cerebrovascular disease or peripheral artery disease), and 253 controls. Occurrence of carotid plaques was investigated with ultrasound. Plasma levels of biomarkers reflecting apoptosis (Fas, TNF receptor 1, TRAIL receptor 2), inflammation (IL-6, IL-8, monocyte chemotactic protein-1), tissue degradation (matrix metalloproteinase (MMP)-1, MMP-3, MMP-7), and tissue repair (platelet-derived growth factor, epidermal growth factor and stem cell factor) were analyzed by Proximity Extension Assay. Results: Subjects with SLE had markedly elevated plasma levels of biomarkers reflecting apoptosis, inflammation and tissue degradation as compared to controls. SLE patients with CVD had higher levels of Fas, TNF receptor 1, TRAIL receptor 2, MMP-1 and -7 than those without CVD. The same associations were found for the presence of a carotid plaque. When controlling for the factors included in the Framingham risk score, all biomarkers except MMP-1 remained associated with the presence of a carotid plaque, while only TRAIL receptor 2 levels remained significantly associated with CVD. Conclusions: Our findings argue that the cardiovascular risk in SLE is associated with increased cell death by apoptosis and tissue degradation. Graphical abstract: Highlights: There is evidence that other mechanisms than LDL-driven inflammation are increasingly important in CVD. Experimental studies have implicated immune responses in the development of atherosclerosis. Several autoimmune diseases are associated with increased CVD risk, suggesting that autoimmunity may contribute to CVD. This study shows that CVD in SLE is associated with elevated levels of biomarkers reflecting apoptosis and tissue degradation. Tissue injury rather than inflammation may be the cause of cardiovascular complications in autoimmune diseases such SLE.